Syntheses, structures and magnetic properties of four manganese(ii) and cobalt(ii) complexes. Issue 48 (17th November 2015) - Hu, Tuoping; Zheng, Baohua; Wang, Xiaoqing; Hao, Xuena
Abstract : Four novel complexes were synthesized by hydrothermal reactions of metal ions and mixed ligands. The magnetic susceptibility of complexes1–4 have been well investigated. Abstract : Hydrothermal reactions of Mn(ii )/Co(ii ) salts and H4 qptc in the presence of corresponding auxiliary N-donor ligands produced four novel complexes, [Mn2 (qptc)(4, 4′-bibp)(H2 O)4 ]·2H2 O n (1 ), [Mn2 (qptc)(1, 4-bib)(H2 O)8 ] n (2 ), [Co2 (qptc)(4, 4′-bimbp)(H2 O)2 ] n (3 ) and [Co2 (qptc)(1, 3-dpp)(H2 O)3 ]·H2 O n (4 ) (H4 qptc = 1, 1′:4′, 1′′:4′′, 1′′′-quaterphenyl-2, 4, 2′′′, 4′′′-tetracarboxylic acid, 4, 4′-bibp = 4, 4′-bis(imidazolyl)biphenyl, 1, 4-bib = 1, 4-bis(1-imidazoly)benzene, 4, 4′-bimbp = 4, 4′-bis(imidazol-1-ylmethyl)biphenyl, 1, 3-dpp = 1, 3-di(4-pyridyl)propane). Single-crystal X-ray diffraction analysis showed that these complexes have different structures, including a 1D chain (2 ), a 2D layered structure (3 ), and a 3D network (1 and4 ), depending on reaction conditions. Complex1 is a 4, 6-connected porous 3D framework with the point symbol (4 4 ·6 2 )(4 4 ·6 10 ·8), which is composed of infinite 2D networks pillared by a 4, 4′-bibp bridging ligand.2 is a 1D zigzag chain, and the adjacent chains extend to a 3D supramolecular structure via non-covalent interactions involving contributions from carboxyl–water clusters.3 is a 2D layer framework with an unprecedented topology, which are packed into a 3D supramolecular architecture by π⋯π and C–H⋯π interactions.4 is a 4, 6-connected 3D network with a Schläfli symbol of (3·4·5 4 )(3 2 ·4·5 5 ·6 6 ·7). Furthermore, the magnetic susceptibility of complexes1–4 have been investigated.1 and4 display weak antiferromagnetic behavior, 2 shows weak ferromagnetic interactions, and3 exhibits different magnetic properties depending on temperature.